Enhanced FOXO1 expression as a predictor of decitabine response and prolonged survival in high-risk myelodysplastic syndrome - Hong Liu; Zheng Zhang; Nanfang Huang; Feng Xu; Sida Zhao; Chunkang Chang (Hematology)
Purpose The aim of this study was to assess the predictive role of FOXO1 expression changes in determining the response to hypomethylation therapy in patients with high-risk myelodysplastic syndrome (MDS).Methods FOXO1 mRNA levels were measured using real-time PCR in 62 newly diagnosed MDS patients undergoing decitabine treatment. The study analyzed the relationship between FOXO1 expression and clinical indicators, treatment outcomes, and prognosis.Results Responders exhibited significantly elevated FOXO1 levels, which were associated with improved peripheral blood counts, decreased bone marrow blasts, and enhanced T-cell immunity and polarization. Increased FOXO1 expression after four cycles of decitabine was associated with a more favorable treatment response. Univariate and multivariate Cox analyses revealed that elevated FOXO1 expression was linked to prolonged overall survival and leukemia-free survival.Conclusions Elevated FOXO1 expression in high-risk MDS patients undergoing decitabine treatment enhances patient prognosis and survival.